Simulation of realistic patella fractures: an investigation into the mechanism and potential benefit for surgical training - Sebastian Wegmann; Jannik Leyendecker; Tim Leschinger; Maximilian Weber; Lars-Peter Mueller; Andreas Harbrecht (Knee Surgery & Related Research)
Abstract Introduction Patella fractures account for about 1% of all bone fractures, predominantly affecting males at a 2:1 ratio and exhibiting distinctive age-related patterns. In younger individuals, these injuries typically result from high-velocity impacts, while in the elderly, they usually arise from lower-energy impacts. Consequently, the types of fractures differ; horizontal fractures are more common in younger individuals, whereas comminuted fractures are more prevalent in older adults. Owing to the knee’s biomechanics, surgical intervention is often necessary. Preserving the articular surface is crucial to prevent retropatellar osteoarthritis, making thorough planning of surgical treatment essential. How can the osteosynthesis of this fracture entity be simulated as realistically as possible? Materials and methods This study focused on the feasibility of inducing realistic patella fractures with an intact soft tissue envelope on human cadaveric specimens for surgical training purposes. A total of seven fresh-frozen human cadaveric knee joints were used, and fractures were created using a custom-designed drop-test bench. The induced fractures were then classified according to the Arbeitsgemeinschaft für Osteosynthesefragen (AO) and Speck and Regazzoni classifications using radiographic and computed tomography (CT) evaluations. In addition, intra-rater and inter-rater reliability were further examined. Results All specimens were successfully fractured. The results demonstrated high intra-rater and inter-rater reliability in both fracture classification systems, indicating that the method can reliably replicate realistic fractures for training purposes. Conclusions The study highlights the significance of using specimens with realistically induced fracture patterns in surgical education. Given that patella fractures are relatively rare and limit direct clinical exposure, realistic fracture models are invaluable for understanding these conditions. These models enhance surgical training, enabling both novice and experienced surgeons to refine their skills and effectively adapt to new surgical techniques.